2022
DOI: 10.1159/000527801
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nogo-A Gene Polymorphisms with Cerebral Palsy in Southern China: A Case-Control Study

Abstract: Cerebral palsy (CP) is a motor and postural disorder syndrome caused by the nonprogressive dysfunction of the developing brain. Previous studies strongly indicated that the Nogo-A gene might be related to the pathogenesis of CP. The objective of this research was to explore the relationship between Nogo-A polymorphisms (rs1012603, rs12464595 and rs2864052) and CP in Southern China. The Hardy-Weinberg equilibrium (HWE) testing, allele and genotype frequencies analysis, and haplotype association analysis were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…We previously collected 120 family blood samples of idiopathic CP, and found highly correlated genes [13] . We also performed Nogo-A gene polymorphism analysis for CP, and found that Nogo-A might affect mild types of CP and there might be sex-related differences [14] . Although it was reported that the diagnostic yield of exome or genome sequencing was 31.1%, the rate may be underestimate as many researches did not conduct family blood test [15] .…”
Section: Risk Factors and Genetic Etiologymentioning
confidence: 99%
“…We previously collected 120 family blood samples of idiopathic CP, and found highly correlated genes [13] . We also performed Nogo-A gene polymorphism analysis for CP, and found that Nogo-A might affect mild types of CP and there might be sex-related differences [14] . Although it was reported that the diagnostic yield of exome or genome sequencing was 31.1%, the rate may be underestimate as many researches did not conduct family blood test [15] .…”
Section: Risk Factors and Genetic Etiologymentioning
confidence: 99%